Análisis de los sistemas de manejo poscosecha en tomate de árbol (solanum betaceum), aplicadas en las plantaciones agrícolas del Cantón Chambo - Alemán Mancheno, Gilda Verónica (2021)
This research aims to analyze the post-harvest system of the species “tree tomato” (solanum betaceum), applied on the agricultural plantations in Chambo, a town located in the Chimborazo province. Through agricultural producers of Chambo, who are registered as such by the Ministry of Agriculture and Cattle Farming (MAG). The study was carried out using research techniques, methods and instruments, and data provided by the Regional Director for MAG, surveying agricultural producers. The protocols used by agricultural tree tomato producers were evaluated, where errors were found, which resulted in the reduction of quality and the loss of the final product. Mainly because 82% of farmers are unaware of the proper post-harvest handling of the product once harvested. A proposal was developed for the optimal post-harvest process of the tree tomato, where it begins with selecting the product and ends with its transport. In addition, 97% of the producers comply with the environmental conditions for product storage. However, 100% of the producers do not have adequate vehicles to transport the product. According to the main findings, there is a need for implementing a program to train producers of “tree tomato” in post-harvest techniques, so losses are prevented, and product quality is boosted